Exploration of Organizational Culture, Knowledge Management, Organizational Effectiveness - Ratnasari, Rajnish; Srivastava, Navin; Rana, Geeta (International Journal of Psychosocial Rehabilitation, 2020)
Rationale: Knowledge Management (KM) is presently considered as a standout amongst the most critical parts of any organization and a Supplement to the organization’s business exercises. With new economy progressively turning into a more learning-based economy, information is turning into the most essential resource for organizational accomplishment among diverse assets. It is imperative to study the association of knowledge management and organizational culture and organizational effectiveness. Purpose/Objective: The purpose of this study is to examine the relationship between organizational culture, knowledge management and organizational effectiveness in IT industry. Also, to examine the role of organizational culture between knowledge management and organizational effectiveness. Design: A well-designed questionnaire based on 5-point Likert scale is used for data collection from 136 employees working in IT industry. Findings: Analysis has concluded that there is a positive correlation between all the dimensions used. Also, the organizational culture plays an important role in exploring the knowledge management which results in organizational effectiveness in the organization. Practical Implications: The research implicates the practical value for culture, knowledge, and usage of collaboration and coherence process on the effectiveness of knowledge management practices within the organization.